Qualitative Analysis on Investment Decisions of Nepalese Stock Market Investors - Rashesh Vaidya (Profesional Muda Cendekia Publishing, 2021)
The paper attempts to examine the experience of the Nepalese investors at the secondary market. The paper explored the investment decisions process of the Nepalese investors. The paper has adopted the grounded theory to generate the theory from the data collected from the semi-structured interview from the stock market investors having an academic background in management. The findings revealed that the investors are eager to invest in the stock market and go for a better experience from their trading at the NEPSE floor. The study exposed a mixed opinion in context to the understanding of the macroeconomic aspects and their influence on investment decisions. The investors forwarded that there is no relation between their investment decision-making process and the macroeconomic factors, while some of the investors stated that they see a connection of the economy with the stock market directly or indirectly. The study came out that the major concern of the Nepalese investors is a fundamental aspect of the listed companies while selecting for an investment. At the same time, investors stated that they go for technical analysis or follow the market trend for the short-term trading at NEPSE floor. The investors are seen at one point that the unstable political situation and insider trading have been major challenges, in context to the Nepalese stock market. Finally, the excessive flow of information related to the listed companies either with some validity or not, makes an investor’s investment decisions go wrong.